Molecular detection and genetic characterization of the potentially pathogenic Coxiella burnetii and the endosymbiotic Candidatus Midichloria mitochondrii in ticks infesting camels (Camelus dromedarius) from Tunisia. (November 2019) - Selmi, Rachid; Ben Said, Mourad; Mamlouk, Aymen; Ben Yahia, Houcine; Messadi, Lilia
Abstract: Tick-borne bacteria are considered to be emerging in camels, but data about their occurrence in Tunisian dromedaries and their infesting ticks remain scarce. In this study, 412 camel blood samples and 327 partially engorged ticks were collected and tested for the presence of Coxiella burnetii and/or related strains, and Rickettsiales bacteria. Coxiella burnetii was detected in 9 Hyalomma impeltatum and 3 H. dromedarii with an overall prevalence rate of 3.6% (12/327). Candidatus Midichloria mitochondrii DNA was identified in 16 H. impeltatum and 10 H. dromedarii with an overall prevalence rate of 8% (26/327). Six ticks (2%) were found to be co-infected with these two bacteria. No positive DNA camel blood sample was observed for both bacteria. Genotyping and phylogenetic analysis of obtained C. burnetii partial sequences based on the IS1111 and htpB genes revealed 99–100% similarity to the pathogenic C. burnetii strains isolated from humans, ruminants and ticks, and that were genetically distant to those isolated from all endosymbiotic related strains ( Coxiella -like bacteria). The analysis of the rickettsial partial sequences of the 16S rRNA gene showed 100% similarity to Ca. M. mitochondrii strains infecting Ixodid ticks and dogs . This is the first time that C. burnetii and Ca. M. mitochondrii have been detected in ticks from Tunisia, which raises the possibility of the involvement of Hyalomma tick species in the active diffusion of these bacteria among camels, other domestic animals and humans. Highlights: Infections of Tunisian camel ticks with Coxiella burnetii (3.6%) and Candidatus Midichloria mitochondrii (8%) occurred. C. burnetii and Ca. M. mitochondrii were detected in Hyalomma ticks for the first time in Tunisia. Single and dual infections were analyzed according to different risk factors. Genotyping of Coxiella burnetii and Ca. M. mitochondrii was performed by using IS111 / htpB and 16S rRNA genes, respectively.